1982
DOI: 10.1136/bmj.284.6315.551
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation in disease activity in rheumatoid arthritis.

Abstract: Disease activity in rheumatoid arthritis as measured by repeated estimation of joint pain, stiffness, articular index, and grip strength was shown to have a circadian rhythm, maximal activity being seen between 0200 and 0400 and minimal activity in the early afternoon. This variation in disease activity may be related to circadian alterations in immune and inflammatory responses (such as immune complexes and neutrophil function) dependent on alterations in circulating concentrations of steroids.The circadian v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
1
3

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(92 citation statements)
references
References 9 publications
(1 reference statement)
4
82
1
3
Order By: Relevance
“…On the basis of the work described here, we propose that induction of low but sustained elevations in plasma cortisol could be an effective treatment for RA. Furthermore, it could be argued that intensive but short-term therapy with cortisol at the onset of RA may abort the subsequent development of the chronic phase of the disease, as has been demonstrated for SCW arthritis in the LEWIN rat (10). Finally, the studies described here suggest that an abnormality in the immune/inflammatory and neuroendocrine loop in patients with RA may be an additional and hitherto unsuspected factor in the immunopathogenesis of this disease.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…On the basis of the work described here, we propose that induction of low but sustained elevations in plasma cortisol could be an effective treatment for RA. Furthermore, it could be argued that intensive but short-term therapy with cortisol at the onset of RA may abort the subsequent development of the chronic phase of the disease, as has been demonstrated for SCW arthritis in the LEWIN rat (10). Finally, the studies described here suggest that an abnormality in the immune/inflammatory and neuroendocrine loop in patients with RA may be an additional and hitherto unsuspected factor in the immunopathogenesis of this disease.…”
Section: Discussionmentioning
confidence: 86%
“…This situation may pertain to RA since it has a pronounced diurnal periodicity of disease activity thought to be dependent on the circadian rhythm of physiologic levels of glucocorticoids (10,11). In addition, work by Neeck et al has shown that although the plasma cortisol concentration in RA is within the normal range, it is inappropriately low for the degree of ongoing inflammation (12).…”
mentioning
confidence: 99%
“…gene within the joitit [29]; treatment of these animals with MoAbs to TNF-a completely abrogated the arthritis [29]. In RA, there is a diurnal rhythm of disease activity [30]. We therefore set out to study the 24-h secretion pattern of TNF-a, TNF-sR55 and TNF-sR75 in patients with active RA.…”
Section: Introductionmentioning
confidence: 99%
“…In rheumatoid arthritis, the peak of disease activity occurs at about 3 AM, and minimal activity occurs 12 hours later. 46 Similarly, the greatest probability of renal allograft rejection occurs between 5 and 8 AM. 47 Those findings may be linked to the seemingly greater immune system activity during this period and may possibly be influenced by the occurrence of low concentrations of immunosuppressive agents, such as corticosteroids, during this critical interval.…”
Section: Discussionmentioning
confidence: 99%